ASSESSMENT OF THE MILK COMPONENTS OF IRAQI DROMEDARY CAMELS - Naqa S. M. Tamimi; Shaoob N.A. AL-Shihani (Basrah Journal of Veterinary Research)
Camels’ milk has gained so many attentions recently because of its unique therapeuticeffects. Iraq is one of the Arab countries with a long history of camel husbandry and few studiesregarding this important products’ compositions. In this study fresh milk samples from 78apparently healthy she camels from Wasit province were collected and analyzed. According tothe results means ± Standard Deviation (SD) for Fat, Protein, and Lactose were 3.48 ± 0.95, 4.23± 1.61 and 4.3 ± 2.56 percent, respectively. In addition, values for Total solids, Solid non-fat,Salt values were 9.0 ± 1.43, 8.64 ± 1.75, and 0.73 ± 0.08 percent, respectively. And means ± SDfor Density was 1.031 ± 0.0032 g/cm3 in this study. Data analysis revealed that sampling datewas correlated with the milk’s fat, density, and pH (p<0.05). She camels’ age was correlatedwith salt values of their milk (p<0.001); while, their parity numbers correlated with the proteinand salt values of the milk (p<0.05). Our findings fell within the published literature with minorvariations; however, higher means for fat, protein and lactose were yielded compared to studiesfrom other countries. Owners should be educated that they could obtain milk with better qualityand higher quantity by improving feeding and husbandry measures.